Understanding the Public Sphere and Women’s Question in Colonial Assam: A Study in its Initial Phases - Sonali Borah; Pallabi Hazarika (Richtmann Publishing, 2023)
Before the advent of the British, the public sphere did not evolve much in India to channelizing the grievances and thoughts of the masses at large. Any discussion related to the state, administration, or any area was confined mostly to the royal court. All the Hindu and Muslim rulers considered themselves supreme and they never sought public opinion. The rational public discussion and places such as coffee houses and salons as suggested by the Habermas as in Western Europe were almost extinct here. As far as the Assam was concerned the growth of almost 170 years of Assamese print media is also linked with the rise of sub-regional nationalism. Most of the public debates were taking place in the print media. So, print media have become an important aspect of the public sphere. The periodicals, starting from Orunudoi onwards had been publishing important topics of society, and women issues were continuously being discussed there. So, analysing the 19th century is important to understand the questions that started on women’s behalf to improve their position in the society. Received: 5 January 2023 / Accepted: 28 February 2023 / Published: 6 March 2023